PROFIL KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI GEOMETRI DITINJAU DARI KECERDASAN VISUAL SPASIAL - Gempur Anarky, Fajar; Sumartono; Prastiwi, Lusiana (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2023)
ABSTRACT Creative thinking is the process of generating many ideas for a problem and providing various possible answers or solutions to a problem based on the information provided. The purpose of this study was to describe the profile of students' creative thinking abilities in geometry material in terms of students' visual-spatial intelligence. This research is a type of descriptive qualitative research conducted at SMA Dr. Soetomo Surabaya for the 2022-2023 academic year, with research subjects for class XII IPA 2 students. To be able to find out a description of students' creative thinking abilities, a test was carried out which contained three indicators of creative thinking, namely fluency, flexibility and originality. There are two stages in this study, namely: giving questions on the visual-spatial intelligence test and giving questions on the ability to think creatively. From the results of the study using triangulation, namely by comparing the results of written tests with interviews, it was shown that: students with high visual-spatial intelligence fulfilled all indicators of creative thinking ability, students with medium-level visual-spatial intelligence only fulfilled two indicators of creative thinking ability, and students with visual intelligence low level spatial meets one indicator of creative thinking ability. Keywords: Creative Thinking, Geometry, and Visual Spatial Intelligence